Mozart's ghosts haunting the halls of musical culture - Everist, Mark 1956- (Oxford University Press, 2013)
In 'Mozart's Ghosts', author Mark Everist investigates how the composer's past status can be understood as part of today's veneration. Everist forges new paths to reach the composer examining a number of ways in which Western culture has absorbed the idea of Mozart, how various cultural agents have appropriated, deployed, and exploited Mozart toward both authoritarian and subversive ends, and how the figure of Mozart and his impact illuminate the cultural history of the last two centuries in Europe, England, and America